Where are all the men? Low energy availability in male cyclists: A review. Issue 11 (2nd November 2021) - Schofield, Katherine L.; Thorpe, Holly; Sims, Stacy T.
Abstract: Most of the low energy availability (LEA) research has been conducted in female populations. The occurrence of LEA in male athletes is not well known, even with an understanding of the components involved in and contributing to LEA. Cycling is a major risk factor for LEA due to inherent sports characteristics: low impact, high energy demands, and a common perception that leanness is a performance advantage. The purpose of this review is to discuss the cycling-specific studies that have documented components of RED-S. The review demonstrates male cyclists (1) experience energy deficits daily, weekly and throughout a season; (2) exhibit lower bone mineral density at the spine compared to the hip, and low bone mineral density correlating with LEA and; (3) demonstrate downregulation of the endocrine system with elevated cortisol, reduced testosterone and insulin-like growth factor 1. The complexity of LEA is further explored by the socio-psychological contribution that may impact eating behaviours, and therefore increase the risk of developing LEA. Future research directions include applying multifaceted research methods to gain a greater understanding of this syndrome and the effect of LEA on male cyclists.